Exploring strategic priorities for regional agricultural R&D investments in East and Central Africa - You, Liangzhi; Johnson, Michael E. (International Food Policy Research Institute, 2008)
Agriculture plays a dominant role in nearly all the countries of East and Central Africa, and many face similar agroecological, climatic, and development challenges. As a result, significant scale economies can be made through the regionalization of research and development (R&D) using networks such as the Association for Strengthening Agricultural Research in Eastern and Central Africa. The challenge for such networks, however, is to determine both regional and national research priorities with the highest potential rates of economic return. Methodology to assess regional research priorities is a critical input into this process, particularly when it comes to weighing likely complementarities among individual research programs, thus maximizing impact across countries at the regional level. This paper presents such an approach using spatial analysis and the Dynamic Research Evaluation for Management (Dream) modeling software, which was developed by the International Food Policy Research Institute to assess potential economic returns to agricultural R&D and guide resource allocation decisions. Dream is applied to the East and Central African region to estimate potential economic and technological spillovers from country- and regional-level R&D investments for select commodities based on future projections of supply and demand, trade flows between countries and world markets, and shared agroecologies and farming systems. The results of the study indicate significant potential for agricultural technology spillovers within the region. Countries will therefore reap greater economic benefits in their search for technology solutions if they pool their resources and pursue regional initiatives for the common good.